Investigation on Operating Parameters of the Homemade Penning-Type Ion Source for Cyclotron - S Silakhuddin; S. Santosa (Atom Indonesia, 2015)
A Penning-type ion source for a cyclotron producing PET radioisotopes has been made. To determine the performance of the ion source for further developments, an investigation on the operating parameters has been conducted. The investigation was carried out by experiments on an ion source test device. The investigated operating parameters were the puller voltage, the magnetic field, the hydrogen gas flow rate, and the cathode current. The results showed that the puller voltage was the most sensitive parameter to change ion beam current, and at a voltage of 8 kV an ion beam current of 35 µA was obtained. The puller voltage is still likely to be raised if the current beam is to be increased. Increasing the magnetic field beyond approximately 450 gauss caused the ion beam to saturate. It was obtained that a moderate range of gas flow rate on the value of 5-10 cc/min, producing a high beam current with no significant effect to decrease a vacuum level. Cathode current magnitudes of up to 1 mA significantly affect the beam current, while above this value the beam current tends to be constantReceived: 04 October 2014; Revised: 28 April 2015; Accepted: 05May 2015